2021
DOI: 10.3390/ijms22168545
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Nerve Regeneration by Exosomes Secreted by Adipose-Derived Stem Cells with or without FK506 Stimulation

Abstract: Exosomes secreted by adipose-derived stem cells (ADSC-exo) reportedly improve nerve regeneration after peripheral nerve injury. Herein, we investigated whether pretreatment of ADSCs with FK506, an immunosuppressive drug that enhances nerve regeneration, could secret exosomes (ADSC-F-exo) that further augment nerve regeneration. Designed exosomes were topically applied to injured nerve in a mouse model of sciatic nerve crush injury to assess the nerve regeneration efficacy. Outcomes were determined by histomorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 74 publications
(94 reference statements)
0
10
0
Order By: Relevance
“…Recent studies have demonstrated the beneficial role of ADSC-EVs in multiple tissue regeneration, such as skin ( 59 ), tendon ( 60 ), bone ( 61 ), and nerve tissue ( 62 ). ADSC-EVs exert a regenerative effect by delivering signals to cells with single or coordinated actions of biomolecules.…”
Section: Mechanisms By Which Adsc-evs Play a Therapeutic Role In Skin...mentioning
confidence: 99%
“…Recent studies have demonstrated the beneficial role of ADSC-EVs in multiple tissue regeneration, such as skin ( 59 ), tendon ( 60 ), bone ( 61 ), and nerve tissue ( 62 ). ADSC-EVs exert a regenerative effect by delivering signals to cells with single or coordinated actions of biomolecules.…”
Section: Mechanisms By Which Adsc-evs Play a Therapeutic Role In Skin...mentioning
confidence: 99%
“…The higher the levels, the more powerful the support for neuron regeneration. Consistently, Rau et al observed significantly increased expression of NGF and GDNF in the nerve segments of crush injury mice after ADSC-Exos treatment, compared with control mice [ 168 ].…”
Section: Exosomes In Peripheral Nerve Repair and Regenerationmentioning
confidence: 72%
“…It was not until recently that exosomes and their impact on SCs have come into focus. Studies have demonstrated that exosomes from various sources can enhance peripheral nerve development and regeneration by activating SCs, regulating their differentiation and proliferation, and inhibiting their apoptosis, as well as optimizing their functions during remyelination [ 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 ].…”
Section: Exosomes In Peripheral Nerve Repair and Regenerationmentioning
confidence: 99%
“…The combined use of FK506 and ADSCs has been used in cell therapy for organ transplantation [38] or vascularized composite allotransplantation [39,40]. In a mouse model of sciatic nerve crush injury, we showed that the topically sprayed exosomes, which were secreted by ADSCs under the condition of FK506 stimulation (ADSC-F-exo), exhibit similar effects to those of ADSC-exo on enhancing nerve regeneration [41]. Under the hypothesis that the topically sprayed ADSC-F-exo around the crush nerve segment can also rescue the autophagy of macrophages in the milieu surrounding the innervated neurons, this study was performed with the aim to assess the effect of ADSC-F-exo treatment on the autophagy of macrophages in the spinal segments following nerve crush injury, with the additional goal of exploring the potential effective proteins inside the exosomes.…”
Section: Introductionmentioning
confidence: 95%